TRANSLATION OF CULTURAL TERMS IN THE NOVEL GADIS PANTAI INTO THE GIRL FROM THE COAST - Nurul Anisa (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
Through the novel Gadis Pantai, Pramoedya Ananta Toer successfully exposes the practices of Javanese feudalism, which lack decency and a sense of humanity. The strong presence of Javanese culture in this novel prompted the author to conduct this study, which aims to identify the cultural terms found in the novel Gadis Pantai translated into English as The Girl From The Coast and to examine the translation procedures employed by the translator. This study is a qualitative descriptive study. The data sources consist of cultural terms found in the novel Gadis Pantai and its English translation. The results show that cultural terms found in the material culture category totaled 52 data points (35%), those in the organizational, customs, and concepts category totaled 48 data points (32%), those in the social culture category totaled 38 data points (25%), and those in the ecological category totaled 12 data points (8%). Furthermore, seven translation procedures were identified, including transference (41 data points, 27.3%), descriptive equivalents (39 data points, 26%), cultural equivalents (34 data points, 22.7%), literal translation (16 instances, 10.6%), couplet (15 instances, 10%), functional equivalence (4 instances, 2.7%), and triplet (1 instance, 0.7%). It can be concluded that the most frequently used translation procedure in this study was transference.